COEXISTENCE OF CLASSICAL MUSIC AND GUGAK IN KOREAN CULTURE - PARK, So Hyun (International Journal of Korean Humanities and Social Sciences, 2020)
Classical music and Korean traditional music ‘Gugak’ in Korean culture try various ways such as creating new music and culture through mutual interchange and fusion for coexistence. The purpose of this study is to investigate the present status of Classical music in Korea that has not been 200 years old during the flowering period and the Japanese colonial period, and the classification of Korean traditional music and musical instruments, and to examine the preservation and succession of traditional Gugak, new Korean traditional music and fusion Korean traditional music. Finally, it is exemplified that Gugak and Classical music can converge and coexist in various collaborations based on the institutional help of the nation. In conclusion, Classical music and Korean traditional music try to create synergy between them in Korean culture by making various efforts such as new attempts and conservation.